THE INFLUENCE OF BASIC PSYCHOLOGICAL NEEDS ON SECONDARY SCHOOL STUDENTS’ INTRINSIC MOTIVATION AT RRI ACTIVITY - Peciuliauskiene, Palmira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article deals with the role of responsible research and innovation (RRI) at science education in promoting intrinsic motivation of secondary school learners from Lithuania. RRI deals with uncertain areas of knowledge and gives students an opportunity for responsibility and self-expression to come to informed decisions about science innovations and their impact. The theoretical background of learners’ intrinsic motivation was analysed on the basis of Self-Determination Theory (STD). STD highlights three basic psychological needs of learners: the need for autonomy, the need for competence and the need for relatedness.The research problem is formulated as a question: how do basic psychological needs influence intrinsic motivation of secondary school learners at RRI activity? Intrinsic motivation inventory was used to assess the secondary school students’ intrinsic motivation related to RRI activity. The collected data were analysed using simple regression. The findings confirm that the need for competence and the need for relatedness are important internal factors in promotion of intrinsic motivation of secondary school learners at RRI activity.